Assessing the seasonal potential of wastewater and rivers as heat sources for district heating: Methodology and example application for the federal state of Hesse, Germany - Sieglar, Joachim; Zipplies, Johannes; Liese, Valerie; Siebert, Nele; Morck, Tobias; Theobald, Stephan; Vajen, Klaus; Jordan, Ulrike (International Journal of Sustainable Energy Planning and Management, 2026)
The transition to a sustainable energy system requires the consideration of all available renewable heat sources. This study assesses the potential of wastewater and river heat for district heating networks in the federal state of Hesse, Germany, considering the seasonality of available heat and heat demand. Using standardised temperature and flow profiles for 443 wastewater treatment plants as well as interpolated river temperature and flow data for approx. 1,500 km of rivers, the study quantifies the heat extraction potential. By matching with heat demand profiles at daily resolution, based on forecast heat demand data for the year 2045, the long-term usable potential is determined. Possible heat network areas are identified based on the heat density indicator. For all building blocks with heat densities above 175 MWh/(ha·a), the usable heat potential amounts to 4.5 TWh/a for river heat pumps and 4.9 TWh/a for wastewater heat pumps. Applying a higher threshold of 415 MWh/(ha·a) reduces the potential to 1.3 TWh/a and 2.4 TWh/a, respectively. The usable potential of both sources together corresponds to 11 % to 28 % of Hesse’s heating demand for space heating and domestic hot water. Using a new 1D energy balance model for an exemplary river it is shown that the heat extraction from the river is acceptable concerning cumulative cooling. The study provides municipalities with a comprehensive database that facilitates the incorporation of these underutilised heat sources into their mandatory heat planning. The methodology presented can be adapted to other regions.